2022
DOI: 10.1039/d1na00839k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell–nanoparticle interactions and imaging of in vitro labeled cells showing barcorded endosomes using fluorescent thiol-organosilica nanoparticles surface-functionalized with polyethyleneimine

Abstract: Biomedical imaging using cell labeling is an important technique to visualize cell dynamics in the body. To label cells thiol-organosilica nanoparticles (thiol-OS) containing fluorescein (thiol-OS/Flu) and containing rhodamine B (thiol-OS/Rho)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Previously, we reported PEI-resistant J774A.1 cells that could not uptake OS/ F-PEI particles very well compared with particles of similar size without PEI. 25 These results indicated that the uptake of J774A.1 cells is controlled not only by surface positive charge but also by particle size and surface structure, and even by a combination of these factors, indicating the uptake selectivity of 774A.1 cells.…”
Section: Time-lapse Microscopic Imaging and Single-cell Analysis Of P...mentioning
confidence: 72%
See 2 more Smart Citations
“…Previously, we reported PEI-resistant J774A.1 cells that could not uptake OS/ F-PEI particles very well compared with particles of similar size without PEI. 25 These results indicated that the uptake of J774A.1 cells is controlled not only by surface positive charge but also by particle size and surface structure, and even by a combination of these factors, indicating the uptake selectivity of 774A.1 cells.…”
Section: Time-lapse Microscopic Imaging and Single-cell Analysis Of P...mentioning
confidence: 72%
“…Previously, we reported that the hydrodynamic diameters of surface-functionalized thiol-organosilica particles (diameter 151 nm) with various molecular weights of PEI showed various increases, but no decrease. 25 Because the diameters of OS/F400PEI and OS/F680PEI did not decrease on STEM (Figure 1 and Table 1), PEI surface functionalization would hasten Brownian motion of particles of OS/F400 and OS/F680, but not OS/F150. PEI surface functionalization could change the structure and interaction with water molecules in a particle-size-dependent manner.…”
Section: Preparation and Characterization Of Fluorescentmentioning
confidence: 94%
See 1 more Smart Citation
“…A dose-dependent increase in the fluorescence intensity of the particles was observed, which was used as a reference to determine the exposure time for the fluorescence microscopy analysis of lung tissue. The fluorescence stability of these particles was previously evaluated, , which showed no predominant changes in particle fluorescence intensity after 24 h of incubation under acidic conditions, indicating good stability in cells after uptake.…”
Section: Resultsmentioning
confidence: 99%
“…This result, in which AC (−)/thiol-OS/Au/PEI and AC300/thiol-OS/Au/PEI show an increase in the cell death ratio on DAY 4 without X-ray irradiation by cell counts and cell viability counts, also shows the same tendency as the results of cell counts. The slight decrease in cell viability for the 4T1 cells treated with AC (−)/thiol-OS/Au/PEI and AC300/thiol-OS/Au/PEI implies the cytotoxicity of the modified-PEI on NPs because AC (−)/thiol-OS/Au/PEI and AC300/thiol-OS/Au/PEI are absorbed more than AC600/thiol-OS/Au/PEI and AC800/thiol-OS/Au/PEI (Table ), indicating that the cytotoxicity of PEI , accelerated the PEI-modified NP uptake.…”
Section: Results and Discussionmentioning
confidence: 99%